Analysis of the application of the lean six sigma method to minimize waste in the plywood production process - Fadila Meriska Putri; Anggriani Profita; Suwardi Gunawan (Jurnal Teknika, 2021)
PT. XYZ is a manufacturing company that produces plywood. The problem that this plywood company has faced is that in the plywood production process, there are still many activities classified as waste, thus disrupting productive activities. Therefore, identification of waste and the factors that cause it must be done to provide improvements so that waste in the production process can be reduced or even eliminated. Efforts that can be made to overcome the problems that occur were by using the lean six sigma method. The most influential waste in the plywood production process is overproduction with a sigma level of 0.00, waiting with a sigma level of 1.52, and defects with a sigma level of 3.85. The factors that cause waste are WIP waste overproduction, waste waiting between the process, and waste defect delamination. The recommendation for improvement for waste to minimize waste is for waste overproduction, namely making digitization forms, waste waiting, adding mini dryers and waste defects, and implementing the Kanban system. PT. XYZ merupakan perusahaan manufaktur yang memproduksi kayu lapis (plywood). Permasalahan yang ditemui pada perusahaan adalah dalam proses produksi plywood masih terdapat aktivitas yang tergolong kedalam waste, sehingga mengganggu kegiatan produktif. Oleh karena itu, identifikasi waste dan faktor penyebabnya perlu dilakukan, sehingga dapat memberikan perbaikan agar pemborosan pada proses produksi dapat dikurangi atau bahkan dihilangkan. Upaya yang dapat dilakukan untuk mengatasi permasalahan tersebut adalah dengan menerapkan metode lean six sigma. Waste yang paling berpengaruh pada proses produksi plywood adalah overproduction dengan level sigma sebesar 0,00, waiting dengan level sigma sebesar 1,52, dan defect dengan level sigma sebesar 3,85. Faktor-faktor penyebab waste adalah untuk waste overproduction WIP, waste waiting between process, dan waste defect delaminasi. Rekomendasi perbaikan untuk waste untuk meminimasi masing-masing waste adalah untuk waste overproduction yaitu membuat form digitalisasi, untuk waste waiting yaitu menambah dryer mini, dan untuk waste defect yaitu untuk menerapkan sistem Kanban.